Nutrition, frailty, and sarcopenia - Cruz-Jentoft, Alfonso J.; Kiesswetter, Eva; Drey, Michael; Sieber, Cornel C. (Aging clinical and experimental research, 2017)
Frailty and sarcopenia are important concepts in the quest to prevent physical dependence, as geriatrics are shifting towards identifications of early stages of disability. Definitions of both sarcopenia and frailty are still developing, and both concepts clearly overlap in their physical aspects. Malnutrition (both undernutrition and obesity) plays a key role in the pathogenesis of frailty and sarcopenia. The quality of the diet along the lifespan has a close relation with the incidence of both entities, and nutritional interventions may be able to reduce the incidence or revert either of them. This brief review explores the role of energy and protein intake and other key nutrients on muscle function. Nutrition may be a key element of multimodal interventions for frailty and sarcopenia. The results of the “Sarcopenia and Physical fRailty IN older people: multi-componenT Treatment strategies” (SPRINTT) trial will offer key insights on the effect of such interventions in frail, sarcopenic older individuals.